Blugold Beginnings Multicultural Learning Community : a Comparison of Campus Involvement and Persistence - Harris, Elizabeth; Czech, Andrew; Wind, Sheina; Nygaard, Abigail (My University, 2013)
Underrepresented students' pathways to college tend to be more challenging, partly because they often have less access to resources, less college knowledge and preparation in the home, and often have to negotiate their identity once attending an institution of higher education (Park, 2007; Perna, 2006). Some of the factors that are correlated with not continuing on to post- secondary education include students' low socio-economic status, being a first-generation student, and also being a student of color (Ishitani, 2003). The Blugold Beginnings Learning Community (BBLC) strives to make the transition from high school to college easier by supporting underrepresented students through high school and facilitating their transitions into college. The Blugold Beginnings Multicultural Learning Community at the University of Wisconsin-Eau Claire was established to help students overcome some of these hurdles. The purpose of this study was: 1) to investigate whether there are differences in personality traits and motivation for obtaining a post-secondary education when comparing students in the program to students in the control group; and 2) to investigate self-reported levels of comfort, academic outcomes, and past experiences on campus by cohort to determine if the learning community students report feeling significantly more confident and connected to campus when compared to their peers who are not a member of the learning community.
Color poster with text, graphs, and charts.
Keywords: College preparation programs--Wisconsin--Eau Claire; Blugold Beginnings (Eau Claire, Wis.); Living Learning Communities (Eau Claire, Wis.); Posters